Correlation of Inter-Canine Width of Maxillary Anterior Teeth with Interpupillary Distance and Inner Inter-Canthal Distance - Dhital, S; Ghimire, B (Journal of Nepalese Prosthodontic Society, 2023)
Introduction: The selection of proper sized maxillary anterior teeth poses a challenge and numerous efforts have been made to develop methods for estimating the inter-canine width of maxillary anterior teeth. In this clinical study, the objective was to investigate the correlation between interpupillary distance (IPD), inner inter-canthal distance (ICAD) and inter-canine width of maxillary anterior teeth (ICW). Methods: The subjects were comfortably seated on a dental chair in a relaxed state in an upright position with the head resting firmly against the headrest. The parameters were measured using a digital caliper. To determine IPD, the midpoint of the pupils was marked and measured. Likewise, the width of ICAD was assessed by measuring between the medial angle of the palpebral fissure of the eyes. The inter-canine width of maxillary anteriors form the distal surface of left and right canines were measured with a dental floss, which was then sectioned and measured. Each parameter was measured thrice, and the average value was calculated and recorded. Results: Mean IPD, ICAD and ICW were 60.8 mm, 31.5 mm and 49.7 mm respectively. Statistical analysis revealed a highly significant difference between IPD and ICW teeth of male and female respectively. Spearman's rho analysis showed statistically significant correlation between ICW and IPD (r=0.156, p =0.006). Similarly, Spearman's rho analysis in male group also showed statistically significant correlation between ICW and IPD (r= 0.374, p=0.00025). Conclusion: This study concluded that there was significant correlation between interpupillary distance and ICW. The measurement of IPD can serve as a valuable reference for guiding the selection and placement of artificial maxillary anterior teeth.